2014
DOI: 10.1039/c3gc41288a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic pyrolysis of individual components of lignocellulosic biomass

Abstract: We report on the catalytic pyrolysis of switchgrass and its three main components (cellulose, hemicellulose and lignin) over H-ZSM5 catalyst. The yields of aromatic hydrocarbons for the three components decreased in the following order: cellulose > hemicellulose ≫ lignin. Moderately higher temperature favored formation of aromatics. The results indicate that H-ZSM5 catalyst did not remove oxygen in an optimal pathway for catalytic pyrolysis of biomass. Dehydration was the dominant oxygen removal mechanism for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
317
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(344 citation statements)
references
References 36 publications
19
317
1
3
Order By: Relevance
“…Catalytic cracking of bio-oil components converted large-molecular-mass compounds into C 1 -C 4 hydrocarbons. A high correlation between the enhanced CO production due to catalytically promoted decarbonylation and decarboxylation and increased production of aromatic hydrocarbons has been reported [19], which is in good agreement with the result of this study. Increase in the catalyst dosage (change of the biomass-to-catalyst ratio from 1:1 to 1:10) resulted in reduced CO 2 production, while the production of C 1 -C 4 hydrocarbons was enhanced.…”
Section: Resultssupporting
confidence: 82%
“…Catalytic cracking of bio-oil components converted large-molecular-mass compounds into C 1 -C 4 hydrocarbons. A high correlation between the enhanced CO production due to catalytically promoted decarbonylation and decarboxylation and increased production of aromatic hydrocarbons has been reported [19], which is in good agreement with the result of this study. Increase in the catalyst dosage (change of the biomass-to-catalyst ratio from 1:1 to 1:10) resulted in reduced CO 2 production, while the production of C 1 -C 4 hydrocarbons was enhanced.…”
Section: Resultssupporting
confidence: 82%
“…On the other hand, an increase in the value of H 2 /CO ratio in the presence of the doped catalysts may indicate that in this case, decomposition of cellulose occurs more readily via decarboxylation than via decarbonylation route comparing to unmodified material [30].…”
Section: Resultsmentioning
confidence: 99%
“…Experimental results showed that the desilicated zeolites produced more aromatic hydrocarbons and less coke in the pyrolysis of beech wood than the parent microporous ZSM-5 (23.2 % aromatics and 44.4 % coke). Wang et al [101] reported the catalytic pyrolysis of switchgrass and its three main components (cellulose, hemicellulose, and lignin) over HZSM-5 catalyst and found that the yields of aromatic hydrocarbons for the three components decreased in the following order: cellulose > hemicellulose > lignin. The formation of hydrocarbon compounds increased the heating values of bio-oils while the elimination of the undesirable oxygenated compounds such as acids and ketones could alleviate the problems caused by acidity and instability of biooils [102][103].…”
Section: Catalytic Pyrolysis Of Biomassmentioning
confidence: 98%